Which Factors Affect Adolescent Food Preferences? - Seray Kabaran; Seyit M. Mercanlıgil (Güncel Pediatri)
Hunger, extreme desire to eat a certain food, taste, price, and convenience are among the main There are various factors that affect food preferences. Hunger, extreme desire to eat a certain food, taste, price, and convenience are among the main factors affecting food preferences. Additionally, general nutritional habits, family, friends, commercials, and availability of the food are also important for food preferences. Also, past experiences with foods are related to preferring or rejecting some foods. Socializing more with increasing age causes change in the food preferences of adolescents. Unhealthy nutrition habits form as a result of the adolescents consuming fast foods, spending time with their friends outside the house, and consuming more ready-made foods. Current developments in the food industry result in an increase in variety and consumption of snacks such as cookies, chocolate, chips, and crackers in adolescents. Considering all these, in this rewiev article, environmental and personal factors affecting food preferences have been investigated. (Journal of Current Pediatrics 2013; 11: 121-7)